Odvzem premoženjske koristi, pridobljene s kaznivim dejanjem, kot zakonodajni, teoretični in praktični problem - Verdel Kokol, Vanja (visokošolska dela, 2021)
There is a significant proportion of criminal offences committed precisely for the purpose of obtaining illegal benefits. Therefore, a rational criminal policy in the permanent counteraction to such crimes requires an efficient and, above all, an ingenious and well-composed system of deprivation of such benefits. At the same time, fundamental constitutional rights must not be interfered with at the expense of effective confiscation of the proceeds of crime. The issue of confiscation of the proceeds of crime focuses on the three main aspects, namely, the interest of the state that the perpetrators do not retain the proceeds of crime, on the other hand, the principles of legality, necessity and proportionality must be met in order to avoid excessive interference with the rights of the defendants, however, greater importance is also given to the protection of the property interests of victims.
Keywords: Disertacije; institucionalna pristojnost; kazenskopravni odvzem; mednarodno sodelovanje; metoda izračuna; Odvzem; Premoženjska korist; primarni obligatorni odvzem koristi; varstvo oškodovancev; začasno zavarovanje